THE EFFECT OF TRANSFORMATIONAL LEADERSHIP ON EMPLOYEE PERFORMANCE: THE MEDIATING ROLE OF WORK MOTIVATION AT MONICA AND LOREN BAKERY - Dita Sofia; Defrizal Defrizal (ZILLZELL MEDIA PRIMA, 2026)
This study analyzes the effect of transformational leadership on employee performance, the effect of work motivation on employee performance, and the mediating role of work motivation at Monica & Loren Bakery. A quantitative approach with path analysis was employed. The sample consisted of 44 employees selected through stratified random and purposive sampling. Data were collected via questionnaires, observation, and literature study. Validity, reliability, classical assumption tests, hypothesis testing, and the Sobel test were conducted using SPSS. The results show that transformational leadership has a positive and significant effect on work motivation (Sig. 0.000) and on employee performance (Sig. 0.000). Work motivation also has a positive and significant effect on employee performance (Sig. 0.000). The Sobel test confirms that work motivation significantly mediates the relationship between transformational leadership and employee performance (Z-count = 4.305 > 1.96). The coefficient of determination (R² = 0.992) indicates that 99.2% of the variation in employee performance is explained by both variables. The study is limited to a single bakery, which may restrict generalizability. Future research should explore other industries and include variables such as organizational culture or job satisfaction. Leaders are advised to adopt transformational behaviors providing inspiration, serving as role models, and supporting individual development to enhance motivation and performance. This research contributes to HRM literature by confirming work motivation as a key mediator in the culinary SME context.